Impact of Attenuation Correction on Quantification Accuracy in Preclinical Whole-Body PET Images - Wanek, Thomas; Schöllbauer, Lara; Filip, Thomas; Mairinger, Severin; Sauberer, Michael; Blaickner, Matthias; Kuntner, Claudia (Frontiers in Physics, 2020)
Background Whole-body PET images can be obtained by using the “step-and-shoot” (SaS) method (using multiple bed positions) or continuous bed motion (CBM). As transmission scans are not always feasible, an alternative method where attenuation data can be generated via emission-based attenuation correction (AC) maps is of interest. The aim of this preclinical study was to investigate the influence of the acquisition method and AC on the quantitation accuracy of [18F]FDG-PET. Methods [18F]FDG-PET phantom images were acquired using either SaS or CBM. Transmission scans were recorded for the SaS method using a 57Co-point source. Emission-based attenuation sinograms were obtained from the image after segmentation and inverse Fourier rebinning. PET images were reconstructed without AC, transmission based (TX-AC) and emission-based (EM-AC) attenuation correction. Moreover, [18F]FDG-PET scans of rats bearing mammary carcinomas acquired using either SaS or CBM were analyzed retrospectively and quantification in tissues was compared. Results Phantom recovery coefficients (RC) varied greatly, ranging from 0.49±0.01 to 1.15 ± 0.07, dependent on acquisition method, reconstruction algorithm and AC method. In CBM acquired images, EM-AC improved quantification accuracy when compared to no-AC images in the phantom studies (RC 0.79±0.02 vs 0.49±0.01, respectively) and in tumors of rats (DMBA model: 1.16±0.42 SUV vs 0.86±0.28 SUV, respectively). Conclusion The method of AC has a strong influence on the quantification of [18F]FDG. Our data indicates that EM-AC improves quantification in images obtained by CBM and SaS. However, the obtained values were still underestimated when compared to TX-AC corrected images.